2021
DOI: 10.1017/s0950268821000984
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to SARS-CoV-2 in Irish hospital healthcare workers

Abstract: Hospital healthcare workers (HCWs) are at increased risk of contracting COVID-19 infection. We aimed to determine the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies in HCWs in Ireland. Two tertiary referral hospitals in Irish cities with diverging community incidence and seroprevalence were identified; COVID-19 had been diagnosed in 10.2% and 1.8% of staff respectively by the time of the study (October 2020). All staff of both hospitals (N = 9038) were invited to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 25 publications
7
30
0
Order By: Relevance
“…New evidence was consistent with prior updates in finding no consistent association between risk for SARS-CoV-2 infection in HCWs and age (13 studies [ 6 , 8 , 10 , 11 , 14–17 , 19 , 22–25 ]), sex (13 studies [ 6 , 8 , 10 , 11 , 13 , 14 , 16 , 17 , 19 , 22–25 ]), or HCW role (15 studies [ 6 , 7 , 11–16 , 19–25 ]) ( Supplement Table 2 ). Also consistent with prior updates, 5 studies done in the United States, Canada, or Ireland found that non-White race (Black, Asian or Asian/Pacific Islander, or combined non-White races) or Hispanic ethnicity was associated with increased risk for infection ( Supplement Table 2 ) ( 6 , 8 , 11 , 15 , 16 ).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…New evidence was consistent with prior updates in finding no consistent association between risk for SARS-CoV-2 infection in HCWs and age (13 studies [ 6 , 8 , 10 , 11 , 14–17 , 19 , 22–25 ]), sex (13 studies [ 6 , 8 , 10 , 11 , 13 , 14 , 16 , 17 , 19 , 22–25 ]), or HCW role (15 studies [ 6 , 7 , 11–16 , 19–25 ]) ( Supplement Table 2 ). Also consistent with prior updates, 5 studies done in the United States, Canada, or Ireland found that non-White race (Black, Asian or Asian/Pacific Islander, or combined non-White races) or Hispanic ethnicity was associated with increased risk for infection ( Supplement Table 2 ) ( 6 , 8 , 11 , 15 , 16 ).…”
supporting
confidence: 82%
“…Thirteen new studies reported on the association between exposures and likelihood of infection ( Supplement Table 3 ) ( 6–8 , 11 , 12 , 14 , 16 , 17 , 19 , 20 , 23–25 ). Seven studies ( 7 , 8 , 12 , 19 , 20 , 23 , 24 ) consistently found that exposure to COVID-19 in a household or private setting was associated with increased risk for SARS-CoV-2 infection in HCWs (adjusted odds ratios [ORs] ranged from 2.55 to 8.98) ( Supplement Table 3 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Detectable antibody to SARS-CoV-2 is an excellent indicator of previous SARS-CoV-2 infection (4). A high proportion of the SARS-CoV-2 infections notified worldwide have been in hospital healthcare workers (HCW) and antibody seroprevalence has been shown to be higher in HCW than in the general population (5)(6)(7). Understanding the transmission and potential immunity dynamics of SARS-CoV-2 in hospitals is important in mitigating transmission at hospital level and adds valuable information to the growing evidence on the transmission patterns of COVID-19 among HCW.…”
Section: Introduction Sars-cov-2 Infection In Hospital Healthcare Wor...mentioning
confidence: 99%
“…The primary purpose of the data collected was to estimate the seroprevalence of past SARS-CoV-2 infection in our HCW population; that analysis was carried separately as part of the PRECISE Study on Prevalence of Antibodies to SARS-CoV-2 in Irish Healthcare Workers ( 14 ). The data presented here are a secondary analysis as part of the PRECISE study, with the aim of comparing the prevalence of anti-SARS-CoV-2 antibodies in the same HCW population in two different assays targeting the anti-nucleocapsid protein, namely, Abbott Architect SARS-CoV-2 IgG assay and Roche Elecsys anti-SARS-CoV-2 immunoassay ( 15 – 17 ).…”
Section: Introductionmentioning
confidence: 99%